A48 Short term impacts of new cycling infrastructure in Sydney, Australia. Issue 2 (June 2015) - Rissel, Chris; Greaves, Stephen; Crane, Melanie; Standen, Chris
Abstract: Background: A natural experiment to evaluate a new separated bicycle path became possible in Sydney, with the City of Sydney building a new 3.7 km separated bicycle path in the inner city in early 2014. We describe the users of the new bicycle path, and examine its short term impacts. Methods: The Sydney Transport and Health Study is designed to evaluate the cycling and health impacts of a new separated bicycle path in inner Sydney, with six monthly bike counts at two intersections, plus individual resident data collection in the intervention area plus a similar comparison area before the bicycle path was built, and at 12 and 24 months. From the 865 baseline study participants, 675 agreed to be re-contacted, and were invited to complete the 12 month on-line questionnaire in September/October 2014 (513 agreed, 76%). Respondents were asked at baseline to identify the type of cyclist they most identified with (high/low intensity recreational/transport rider), cycling frequency (weekly or less than weekly) plus demographic information. At 12 month follow-up cycling frequency and perceptions of changes in the environment were asked. Chi square tests were used to compare cycling frequencies, and perceptions of the environment. Logistic regression was used to identify factors associated with use of the new bicycle path, with rider type, cycling frequency, age, sex and education in the model. Results: Bike counts reported a 12 month increase of 23% and 97%. There was no change in the self-reported weekly frequency of cycling. One in five (15%) residents had used the new bicycle path, with most (76%) living in the intervention area. Bicycle path users were most likely to be high intensity recreational rider (adjusted odds ratio (AOR) 3.00, 95% confidence interval (CI) 1.16-7.80) or a low intensity transport rider (AOR=2.78, 95%CI 1.44-5.39) had ridden their bicycle in the past week (AOR=5.29, 95% CI 2.96-9.45) and less likely to be older (AOR 0.97, 95% CI 0.95-0.99). Perceptions that the neighbourhood was more pleasant, that there were more people walking and cycling were significantly higher in the intervention area (p<0.05). Conclusions: Increases in resident cycling frequency may require some time, or additional promotional activities. Perceptions of increased cycling may be due to increased cyclists from outside the study area using the new path. Better connectivity of the new path with the City of Sydney bicycle path network may increase cycling frequency.